Analysis of Effective Communication Tools for Disaster Management in the Educational Institutes - Diyal, Suresh Bahadur (Innovative Research Journal, 2023)
Disasters come across as a black day to any country or place within the country. It causes various destructions in the geographical and life of people. Analyze the uses of Information and Communication Technology (ICT) tools in the disaster period, explore the effective communication channel used in disaster management, and identify the best communication tools and channels in disaster periods in educational institutes' main objectives of this study and the Kathmandu, Lalitpur, Bhaktapur, and Dadeldhura districts of Nepal are the main study area. During the disaster period, the government brings different communication tools and awareness programs to minimize risk and destruction. However, due to a lack of proper implementation and unawareness, using those tools effectively has become a major challenge. There are challenges for integrating ICT tools for disaster management because of a lack of knowledge about the ICT tools, and how to use them inappropriately. Social media, smartphones, and short message service (SMS) ICT tools help to communicate immediately during the disaster period. ICT tools helped with disaster management in the research area’s schools and they give priority to the wireless channel then the telephone channel for communication. In some of the schools, there are optical fibers also used for communication and no school used satellite communications channels for communication.